1981
DOI: 10.1542/peds.67.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Can the Physician Diagnose Hyperactivity in the Office?

Abstract: Office diagnosis of hyperactivity can present a problem to the pediatrician because only about 20% of the potential patients show hyperactive behavior during office examination. Exclusion of the children who appear normal in the physician's office can eliminate from medical treatment a large number of patients for whom treatment is appropriate. Eighty percent of the children ultimately accepted into the project on the basis of home and school reports showed exemplary behavior and no sign of hyperactivity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In that case the ADD and ADDH samples in this study would be an ar tifact of the circumstance that hyperac tive children often do not display inap propriate behavior during a one-to-one interview with a clinician. 51 Accounting in this manner fo r this study's failure to find diffe rences between groups labeled ADD and ADDH in essence argues that there exist two groups of troubled chil dren , those who have ADD and those who have ADDH, but that frequently only the behavior of the ADDH children is inappropriate enough to cause them to be referred fo r clinical treatment. Hence, separating those re f erred chil dren into groups labeled ADD and ADDH is misleading.…”
Section: Discussionmentioning
confidence: 83%
“…In that case the ADD and ADDH samples in this study would be an ar tifact of the circumstance that hyperac tive children often do not display inap propriate behavior during a one-to-one interview with a clinician. 51 Accounting in this manner fo r this study's failure to find diffe rences between groups labeled ADD and ADDH in essence argues that there exist two groups of troubled chil dren , those who have ADD and those who have ADDH, but that frequently only the behavior of the ADDH children is inappropriate enough to cause them to be referred fo r clinical treatment. Hence, separating those re f erred chil dren into groups labeled ADD and ADDH is misleading.…”
Section: Discussionmentioning
confidence: 83%
“…Yet measurement issues cloud the viability of these findings, in that initial aggression was indexed by behavior ratings from the psychologists who performed the cognitive testing. Such individualized appraisals of externalizing behavior in the laboratory, doctor's office, or testing room are not sensitive indicators (see, for example, Sleator & Ullmann, 1981). Because more valid indexes might have altered the paths, the unidirectional link of Schonfeld et al from verbal deficits to conduct disorder should be viewed cautiously.…”
Section: Causal Pathways and Underlying Mechanismsmentioning
confidence: 99%
“…Lobitz and Johnson (1975) found that parent reports of young children's behavior problems were able to correctly classify 90% of clinic-referred children and 90% of nonreferred children, and neither lab-based nor home observations of child behavior added much to this prediction. Similarly, in a classic study of ADHD, Sleator and Ullman (1981) demonstrated that observations of behavior in a physician's office often failed to agree with parent and teacher reports and did not aid in the prediction of future problems. In fact, Sleator and Ullman cautioned that overreliance on observational data may actually interfere with the accuracy of the diagnostic process.…”
Section: Aspects Of Incremental Validity In Child and Adolescent Asse...mentioning
confidence: 99%